National clinical audit for hospitalised exacerbations of COPD. Issue 3 (21st September 2020) - Hurst, John R.; Quint, Jennifer K.; Stone, Robert A.; Silove, Yvonne; Youde, Jane; Roberts, C. Michael
Introduction: Exacerbations of COPD requiring hospital admission are burdensome to patients and health services. Audit enables benchmarking performance between units and against national standards, and supports quality improvement. We summarise 23 years of UK audit for hospitalised COPD exacerbations to better understand which features of audit design have had most impact. Method: Pilot audits were performed in 1997 and 2001, with national cross-sectional audits in 2003, 2008 and 2014. Continuous audit commenced in 2017. Overall, 96% of eligible units took part in cross-sectional audit, 86% in the most recent round of continuous audit. We synthesised data from eight rounds of national COPD audit. Results: Clinical outcomes were observed to change at the same time as changes in delivery of care: length of stay halved from 8 to 4 days between 1997 and 2014, alongside wider availability of integrated care. Process indicators did not generally improve with sequential cross-sectional audit. Under continuous audit with quality improvement support, process indicators linked to financial incentives (early specialist review (55–66%) and provision of a discharge bundle (53–74%)) improved more rapidly than those not linked (availability of spirometry (40–46%) and timely noninvasive ventilation (21–24%)). Conclusion: Careful piloting and engagement can result in successful roll-out of cross-sectional national audit in a high-burden disease. Audit outcome measures and process indicators may be affected by changes in care pathways. Sequential cross-sectional national audit alone was not generally accompanied by improvements in care. However, improvements in process indicators were seen when continuous audit was combined with quality improvement support and, in particular, financial incentives. National audit in COPD is feasible and can improve process indicators, particularly when continuous audit is associated with quality improvement initiatives and financial incentives https://bit.ly/3eiOvOY